PRE-DESIGN OF BAMBOO DRYING INDUSTRY FOR SMALL INDUSTRIES: EFFECT OF BAMBOO FORM VARIETIES AND DURATION OF FUMIGATION TIME ON PHYSICAL, CHEMICAL, MECHANICAL AND FUNGAL PROPERTIES OF BETUNG BAMBOO (DENDROCALAMUS ASPER) - Zulvian Hikmatiar, Arelanda
Betung bamboo (Dendrocalamus asper) is one type of bamboo that is often utilised as a raw material for structural structural raw material. This research aims to determine the effect of the shape of bamboo and the length of time of smoking on the physical, mechanical and chemical properties of betung bamboo. This smoking process uses a simple furnace that can be used on a small industrial/home industry scale. can be used on a small industrial/home industry scale. There are 2 types of variables carried out, namely the effect of the shape of the bamboo cut during smoking and the length of time for smoking. and the length of time of smoking. There are 7 tests carried out, namely testing moisture content, density, weight loss, colour testing, MOR and MOE testing, chemical testing using FTIR and fungal resistance testing. chemical testing using FTIR and mould resistance test. The highest moisture content obtained in the control treatment (without smoking) of 13.30% and for the lowest water content in the log shape treatment. lowest water content in the treatment of log pieces with a length of time for fumigation for 2 days as much as 4.23%. in the treatment density test bamboo stick shape and fumigation for 2 days has the highest density value. highest density value. For testing the value of weight loss, treatment with bamboo log shape has the greatest weight loss value (54.90%), and the control treatment had the lowest weight loss value (0%) for colour testing. colour testing of each treatment, both the effect of cut shape and length of time for time did not produce a significant difference. In the mechanical testing of MOR and MOE, the treatment with log-shaped cut shape and fumigation was carried out.